HUBUNGAN ANTARA KEKUATAN OTOT TUNGKAI DENGAN HASIL LOMPAT JANGKIT SISWA PUTRA KELAS XI IPS 1 SMAN 1 KAMPAR - Rusmawati '; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :Problem in this research is the triple jump result male students class XI 1 Social Science of SMAN 1 Kampar not good enough.This suspected because of legs muscles strength fache. Therefore, the aims this research to found out legs muscles strength corelation with triple jump result male students class XI 1 Social Science of SMAN 1 Kampar. This type of research is a corelational, his done in SMAN 1 Kampar with 12 people male student class XI 1 Social Science of SMAN 1 Kampar. Data collected by leg dinamometer for measuring legs muscles strength, and triple jump test. While the analysis data used corelation product moment. Based on analysis result showed rxy 0,7246 it mean there is corelation betwen variable X and Y on enough category, In the end, the condution in this research. Is there are corelation between legs muscles strength with triple jump results male student class XI 1 Social Science SMAN 1 Kampar.Key word : Leg muscles strenght, triple jump result.